Mast Cells Are Activated by Streptococcus pneumoniae In Vitro but Dispensable for the Host Defense Against Pneumococcal Central Nervous System Infection In Vivo - Fritscher, Johanna; Amberger, Daniel; Dyckhoff, Susanne; Bewersdorf, Jan Philipp; Masouris, Ilias; Voelk, Stefanie; Hammerschmidt, Sven; Schmetzer, Helga Maria; Klein, Matthias; Pfister, Hans-Walter; Koedel, Uwe (Frontiers in Immunology, 2018)
Mast cells reside on and near the cerebral vasculature, the predominant site of pneumococcal entry into the central nervous system (CNS). Although mast cells have been reported to be crucial in protecting from systemic bacterial infections, their role in bacterial infections of the CNS remained elusive. Here, we assessed the role of mast cells in pneumococcal infection in vitro and in vivo. In introductory experiments using mouse bone marrow-derived mast cells (BMMC), we found that [i] BMMC degranulate and release selected cytokines upon exposure to Streptococcus (S.) pneumoniae, [ii] the response of BMMC varies between different pneumococcal serotypes and [iii] is dependent on pneumolysin. Intriguingly though, apart from a slight enhancement of cerebrospinal fluid (CSF) pleocytosis, neither two different mast cell-deficient Kit mutant mouse strains (WBB6F1-KitW/Wv and C57BL/6 KitW-sh/W-sh mice) nor pharmacologic mast cell stabilization with cromoglycate had any significant impact on the disease phenotype of experimental pneumococcal meningitis. The incomplete reversal of the enhanced CSF pleocytosis by local mast cell engraftment suggests that this phenomenon is caused by other c-Kit mutation-related mechanisms than mast cell deficiency. In conclusion, our study suggests that mast cells can be activated by S. pneumoniae in vitro. However, mast cells do not play a significant role as sentinels of pneumococcal CSF invasion and initiators of innate immunity in vivo.